TUJUH BELAS TAHUN PENELITIAN AKUNTANSI SYARIAH DI INDONESIA: BIBLIOGRAFI - Rivanti, Nabilla; Natali, Mas Ayu Desvinta; Maharani, Syafrina Devi; Herawati, Nurul (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
This study maps the development of 210 sharia accounting studies in Indonesia published in nationally accredited journals SINTA 1 and 2 for the period 2008-2024. This study uses the field charting method. The classification of sharia accounting topics is divided into 10, namely 1) Sharia institutions, 2) Accounting information system design, 3) Accounting information processing, 4) Standard setting, 5) Organizational sociology, 6) Islamic ethics and accounting, 7) Education, 8) auditing, 9) Historical/categorical/future research, and 10) Sharia accounting concepts. The research methods are classified into 3. Topic mapping found that the dominant topics in sharia accounting research are sharia institutions, sharia accounting concepts, and organizational sociology. On the other hand, sharia accounting topics that are still rarely studied are auditing and education. Mapping of research methods used in sharia accounting research found that sharia accounting research methods are dominated by qualitative methods (51.4%) and quantitative methods (48.1%). Mixed methods are still rarely used in sharia accounting research over the past 17 years. The novelty of this research is the focus of mapping topics and research methods on sharia accounting articles published in accredited national journals and provides an overview of future opportunities for sharia accounting research in Indonesia.